2018
DOI: 10.1093/mnras/sty3479
|View full text |Cite
|
Sign up to set email alerts
|

A re-establishing jet during an X-ray re-brightening of the Be/X-ray binary Swift J0243.6+6124

Abstract: Transient Be/X-ray binary systems, wherein a compact object accretes from a Becompanion star, can show giant and periastron outbursts. During the decay of their giant outbursts, some Be/X-ray binaries also show X-ray re-brightenings, the origin of which is not understood. Recently, we presented the discovery of a jet from a neutron star Be/X-ray binary, observed during the giant outburst of Swift J0243.6+6124. Here, we present continued radio monitoring of its 2017/2018 giant outburst decay and a re-brightenin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 98 publications
1
13
0
Order By: Relevance
“…It is important to note that this pulsar launched a jet when the X-ray luminosity was ≥4×10 36 erg s −1 during giant and fainter outbursts (for a distance of 7 kpc; van den Eijnden et al 2018Eijnden et al , 2019. At the same time, the luminositydependent emission lines were observed in the spectral range of NICER.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…It is important to note that this pulsar launched a jet when the X-ray luminosity was ≥4×10 36 erg s −1 during giant and fainter outbursts (for a distance of 7 kpc; van den Eijnden et al 2018Eijnden et al , 2019. At the same time, the luminositydependent emission lines were observed in the spectral range of NICER.…”
Section: Discussionmentioning
confidence: 75%
“…We also explored the correlation between Fe-line emission and the radio flux density as observed with VLA ( Figure 6). The radio data used here are taken from van den Eijnden et al (2018) and van den Eijnden et al (2019). The VLA observations were quasi-simultaneous to NICER pointings (Ob-sID 1050390105, 1050390116, 1050390118, 1050390122, 1050390134, and 1050390143) between 2017 October and 2018 February.…”
Section: Evolution Of Iron Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that, as discussed extensively in van denEijnden et al (2018b) andvan den Eijnden et al (2019), the observed radio properties (flux densities, spectral shape, and evolution) through-MNRAS 000, 1-14(2018)…”
mentioning
confidence: 60%
“…It reached super-Eddington X-ray luminosities during the peak of its outburst (van den Eijnden et al 2018b) and has been referred to as the first Galactic ULX pulsar by both Tsygankov et al (2018) and Wilson-Hodge et al (2018). Through Very Large Array (VLA) radio and Swift X-ray monitoring, Sw J0243 was found to launch a relativistic jet during its super-Eddington state (van den Eijnden et al 2018b), as well as at lower accreting rates (van den Eijnden et al 2019). This jet detection constituted the first from a strongly-magnetized neutron star, contrary to the predictions of neutron star jet formation theory (Blandford & Payne 1982;Massi & Kaufman Bernadó 2008).…”
Section: Introductionmentioning
confidence: 99%